The Water Content Drives the Susceptibility of the Lichen Evernia prunastri and the Moss Brachythecium sp. to High Ozone Concentrations - Andrea Vannini; Giulia Canali; Mario Pica; Cristina Nali; Stefano Loppi (Biology, 2020)
The aim of this study was to evaluate the tolerance of lichens (Evernia prunastri) and mosses (Brachythecium sp.) to short-term (1 h), acute (1 ppm) O3 fumigation under different hydration states (dry, <10% water content, metabolism almost inactive; wet, >200% water content, metabolism fully active). We hypothesized that stronger damage would occur following exposure under wet conditions. In addition, we checked for the effect of recovery (1 week) after the exposure. Ozone fumigation negatively affected the content of chlorophyll only in wet samples, but in the moss, such a difference was no longer evident after one week of recovery. Photosynthetic efficiency was always impaired by O3 exposure, irrespective of the dry or wet state, and also after one week of recovery, but the effect was much stronger in wet samples. The antioxidant power was increased in wet moss and in dry lichen, while a decrease was found for wet lichens after 1 week. Our results confirm that the tolerance to O3 of lichens and mosses may be determined by their low water content, which is the case during the peaks of O3 occurring during the Mediterranean summer. The role of antioxidant power as a mechanism of resistance to high O3 concentrations needs to be further investigated.